Oxygen reduction catalyst for constructing local'alkaline-like 'microenvironment as well as preparation method and application of oxygen reduction catalyst
By building the "alkaline" micro -environment in the oxygen repayment catalyst, the problem of low oxygen reduction response and stability in natural seawater in the natural seawater has been solved. Application.
Patent Information
- Application Number
- CN202411480831.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-23
AI Technical Summary
Existing oxygen reduction catalysts are low in efficiency and poor stability in natural seawater. In particular, Fe single-atom catalysts have reduced activity due to low ionic conductivity and chloride ion adsorption, which limits the application of seawater metal air batteries.
By putting the FE load on the kernel MOF material, and through the extension growth method, the metal atom with activated water capabilities is built in the shell MOF material, forming the FE/MOF@M/MOF front drive of the nuclear shell structure, and then the original position is performed through the thermal solution. Carbon conversion, obtaining feenc@mnc oxygen repayment catalyst, building a "alkaline" micro -environment.
The catalyst has significantly improved the efficiency and stability of the oxygen reaction in natural seawater, enhanced the output power and service life of the seawater metal air battery, and promoted the practical development of seawater metal air batteries.
Smart Images

Figure CN119361730A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present application relate to the field of material synthesis technology, and in particular to an oxygen reduction catalyst for constructing a local "alkaline-like" microenvironment, and a preparation method and application thereof. Background Art
[0002] Seawater metal-air battery is a new type of battery device that directly uses natural seawater as electrolyte, common metals such as zinc, magnesium, and aluminum as anode, and oxygen reduction electrocatalyst as cathode. It has outstanding advantages such as high theoretical energy density, safe use, low price, and abundant positive electrode metal resources. Therefore, seawater metal-air battery has broad application prospects in ocean observation equipment, island power supply, and small submersibles.
[0003] Oxygen reduction reaction is the core reaction of seawater metal-air batteries, which determines the efficiency and output power of seawater metal-air battery devices during use. Pt-based catalysts are the most effective oxygen reduction catalysts, but their high cost, low reserves and poor durability restrict their large-scale promotion and application in seawater metal-air batteries. Fe single-atom catalysts are considered to be one of the most effective catalysts in oxygen reduction reactions due to their high atomic utilization, clear and uniform active sites, and unique electronic structure. They are also inexpensive. However, in natural seawater systems, due to their low ionic conductivity, seawater metal-air batteries have the problem of slow oxygen reduction reaction. In addition, Fe single atoms are affected by chloride ion adsorption, resulting in reduced catalyst stability and activity. Therefore, it is urgent to develop a synthetic strategy for oxygen reduction catalysts that construct a local "quasi-alkaline" microenvironment to achieve efficient and stable oxygen reduction catalysis in natural seawater. Summary of the invention
[0004] In view of this, the embodiments of the present application provide an oxygen reduction catalyst for constructing a local "quasi-alkaline" microenvironment, and a preparation method and application thereof. The oxygen reduction catalyst overcomes the challenges of low ionic conductivity and chloride ion adsorption in natural seawater, enhances the stability and activity of the catalyst in seawater, improves the efficiency and output power of seawater metal-air batteries, achieves efficient and stable oxygen reduction, promotes the practical development of seawater metal-air batteries, and can effectively overcome the defects of the above-mentioned prior art.
[0005] The first aspect of the embodiment of the present application provides a method for preparing an oxygen reduction catalyst for constructing a local "alkaline-like" microenvironment, comprising the following steps:
[0006] (1) Fe is loaded on the core MOF material to obtain the core Fe / MOF material, and then the metal atom M with water activation ability is in situ constructed on the shell MOF material by epitaxial growth method to obtain the core-shell structured Fe / MOF@M / MOF precursor material, in which Fe and M are confined in the core and shell, respectively;
[0007] (2) The Fe / MOF@M / MOF precursor material was in situ carbon converted by pyrolysis to obtain the FeNC@MNC oxygen reduction catalyst that constructed a local "alkaline-like" microenvironment in natural seawater.
[0008] In some embodiments that may include the above embodiments, in step (1), the metal atom M having the ability to activate water is at least one of Cu, Ni, and Zn. Considering that Cu has a stronger ability to activate water, Cu is more preferably used, but other metals having the ability to activate water are also suitable for this application.
[0009] In some embodiments that may include the above embodiments, in step (2), the pyrolysis temperature is 800-1000° C., and the pyrolysis time is 1-4 h, preferably 1-3 h.
[0010] In some embodiments that may include the above embodiments, in step (1), the MOF materials in the inner core Fe / MOF material and the outer shell M / MOF material are both ZIF-8.
[0011] During the pyrolysis process, Fe and Cu were in situ confined in the core-shell double-layer carbon support, which inhibited the migration of Fe and Cu, and thus formed an oxygen reduction catalyst with the core layer loaded with Fe single atoms with oxygen reduction activity and the shell layer loaded with Cu single atoms with the ability to activate water.
[0012] In some embodiments that may include the above embodiments, the preparation process of the core Fe / MOF material is:
[0013] Dissolve Zn(NO3)2·6H2O and Fe(C5H7O2)3 in methanol and disperse them by ultrasonic, which is called solution A. Dissolve C4H6N2 in methanol and call it solution B. Pour solution A into solution B slowly and stir slowly. After the reaction is completed, collect the precipitate by centrifugation, wash it with methanol several times, and vacuum dry it overnight to obtain the core Fe / MOF material.
[0014] In some embodiments that may include the above embodiments, the preparation process of the Fe / MOF@M / MOF precursor material with a core-shell structure is:
[0015] The core Fe / MOF material is dispersed in methanol, recorded as solution C; Cu(C5H7O2)2 is dissolved in methanol and ultrasonically dispersed, recorded as solution D; C4H6N2 is dissolved in methanol, recorded as solution E; solution D and solution E are slowly poured into solution C respectively, and slowly stirred, recorded as solution F; Zn(NO3)2·6H2O is dissolved in methanol and ultrasonically dispersed, recorded as solution G; solution G is added to solution F, and slowly stirred. After the reaction is completed, the precipitate is collected by centrifugation, washed several times with methanol by centrifugation, and vacuum dried overnight to obtain a Fe / MOF@M / MOF precursor material with a core-shell structure.
[0016] In some embodiments that may include the above embodiments, in step (1), the mass ratio of Fe, core MOF material, M and shell MOF material is 5:30:1:10. By controlling the thickness of the shell MOF material, the best performance is screened.
[0017] The second aspect of the embodiment of the present application also provides an oxygen reduction catalyst for constructing a local "quasi-alkaline" microenvironment, which is prepared by the above method.
[0018] The third aspect of the embodiments of the present application also provides the application of the above-mentioned oxygen reduction catalyst for constructing a local "alkaline-like" microenvironment in a seawater metal-air battery.
[0019] Compared with the prior art, the embodiments of the present application have the following beneficial effects:
[0020] The core of this application is to synthesize a catalyst with the ability to activate water, thereby constructing a local "quasi-alkaline" microenvironment, overcoming the challenges of low ionic conductivity and chloride ion adsorption in natural seawater, enhancing the stability and activity of the catalyst in seawater, achieving efficient and stable oxygen reduction, and promoting the practical development of seawater metal-air batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0022] Figure 1 Synthesis flow chart of the core-shell FeNC@CuNC catalyst that constructs a localized “alkaline-like” microenvironment for this application;
[0023] Figure 2 This is an X-ray diffraction pattern of the core-shell FeNC@CuNC catalyst synthesized in Example 1 of the present application;
[0024] Figure 3 TEM image of the core-shell FeNC@CuNC catalyst synthesized in Example 1 of the present application;
[0025] Figure 4 This is a spherical aberration diagram of the core-shell FeNC@CuNC catalyst synthesized in Example 1 of the present application;
[0026] Figure 5 This is a diagram showing the catalytic performance of the core-shell FeNC@CuNC catalyst synthesized in Example 1 of the present application, the catalyst in Comparative Examples 1-2, and commercial Pt / C for oxygen reduction reaction. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0028] Unless otherwise specified, the experimental methods used in the examples of this application are all conventional methods.
[0029] In the following examples and comparative examples, unless otherwise specified, all raw materials can be obtained by commercial purchase or conventional methods.
[0030] The present application provides a method for synthesizing an oxygen reduction catalyst for constructing a local "quasi-alkaline" microenvironment, firstly by synthesizing a core layer MOF precursor loaded with Fe single atoms; then by epitaxial growth, metal atoms with the ability to activate water are loaded on the shell MOF, and then by high-temperature in-situ carbon conversion, a core-shell FeNC@CuNC catalyst for constructing a local "quasi-alkaline" microenvironment is obtained (after pyrolysis of the Fe / MOF@Cu / MOF precursor material, Fe and Cu are confined on the core layer NC carrier and the shell layer NC carrier, respectively, wherein NC is nitrogen-doped carbon, and dimethylimidazole added to synthesize ZIF-8 provides nitrogen and carbon elements, which are converted into nitrogen-doped carbon carriers after high-temperature pyrolysis).
[0031] Among them, the "metal atom capable of activating water" can be selected according to actual needs, and is not limited to the Cu atom selected in the following examples. In addition, based on the synthesis method proposed in this application, those skilled in the art can select different reagents and method steps to achieve it according to actual needs, and are not limited to the specific reagents and condition parameters used in the following examples.
[0032] Among them: constructing a local "quasi-alkaline" microenvironment means: inducing the OH bonds of water molecules to break and form active OH bonds through metals with the ability to activate water - , while Fe single-site ions react with OH - It has a strong adsorption capacity, which can build a "quasi-alkaline" local microenvironment around the Fe single atom active center.
[0033] Example 1: Synthesis of core-shell FeNC@CuNC catalyst
[0034] 1. Synthesis of core-shell Fe / MOF@Cu / MOF precursor
[0035] i. Synthesis of core layer Fe / MOF precursor
[0036] 1.16g of Zn(NO3)2·6H2O and 0.2g of Fe(C5H7O2)3 were dissolved in 50mL of methanol and ultrasonicated for 10min, which was recorded as solution A. 1.314g of C4H6N2 was dissolved in 50mL of methanol, which was recorded as solution B. Then solution A was slowly poured into solution B and stirred slowly for 12h. After the reaction was completed, the precipitate was collected by centrifugation at 9000rpm and washed three times with methanol. The obtained product was dried under vacuum overnight to obtain a light yellow solid, which was the core layer Fe / MOF.
[0037] ii. Synthesis of core-shell Fe / MOF@Cu / MOF precursor
[0038] 200 mg of Fe / MOF was dispersed in 50 mL of methanol, which was recorded as solution C. 0.1 g of Cu(C5H7O2)2 was added to 50 mL of methanol, and the mixture was ultrasonicated for 10 minutes to make it uniformly dispersed, which was recorded as solution D. 0.657 g of C4H6N2 was added to 20 mL of methanol to dissolve, which was recorded as solution E. Subsequently, solutions D and E were slowly poured into C respectively, and slowly stirred for 12 hours, which was recorded as solution F. Then 0.58 g of Zn(NO3)2·6H2O was added to 20 mL of methanol, ultrasonically dispersed for 10 minutes, which was recorded as solution G. Then solution G was added to solution F and slowly stirred for 6 hours. After the reaction was completed, the precipitate was collected by centrifugation at 9000 rpm, washed 3 times with methanol, and the obtained product was dried overnight under vacuum to obtain a light yellow solid, which was the core-shell Fe / MOF@Cu / MOF precursor.
[0039] 2. Synthesis of core-shell FeNC@CuNC catalysts
[0040] The core-shell Fe / MOF@Cu / MOF precursor was placed in a tube furnace and pyrolyzed at 900 °C for 2 hours under Ar atmosphere to obtain the core-shell FeNC@CuNC catalyst. The synthesis flow chart of the core-shell FeNC@CuNC catalyst with a local "alkaline-like" microenvironment is shown in the figure. Figure 1 shown.
[0041] Figure 2 This is an X-ray diffraction pattern of the core-shell FeNC@CuNC catalyst synthesized in the examples of this application; Figure 3 This is a TEM image of the core-shell FeNC@CuNC catalyst synthesized in the present example. The FeNC@CuNC catalyst synthesized in this example does not have metal particles, and a core-shell structure can be observed.
[0042] The spherical aberration of FeNC@CuNC catalyst is shown in Figure 2. Figure 4 As shown, scattered metal atoms can be found in the red framed position, and it can be considered that the metal exists in the form of single atoms.
[0043] The catalytic performance of the prepared catalyst for oxygen reduction reaction was tested by cyclic voltammetry scanning in oxygen-saturated natural seawater at a scan rate of 5 mV / s and an electrode speed of 1600 r / min using a three-electrode system. Figure 5 As shown, the prepared core-shell FeNC@CuNC catalyst exhibited good catalytic performance for oxygen reduction reaction.
[0044] Example 2
[0045] The synthesis provided in this embodiment can refer to Example 1, except that the metal atom M having the ability to activate water is Ni.
[0046] Example 3
[0047] The synthesis provided in this embodiment can refer to Example 1, except that the metal atom M having the ability to activate water is Zn.
[0048] Comparative Example 1: Synthesis of core-shell FeNC@NC catalyst
[0049] 1. Synthesis of core-shell Fe / MOF@MOF
[0050] i. Synthesis of core layer Fe / MOF precursor
[0051] 1.16g of Zn(NO3)2·6H2O and 0.2g of Fe(C5H7O2)3 were dissolved in 50mL of methanol and ultrasonicated for 10min, which was recorded as solution A. 1.314g of C4H6N2 was dissolved in 50mL of methanol, which was recorded as solution B. Then solution A was slowly poured into solution B and stirred slowly for 12h. After the reaction was completed, the precipitate was collected by centrifugation at 9000rpm and washed three times with methanol. The obtained product was dried under vacuum overnight to obtain a light yellow solid, which was the core layer Fe / MOF.
[0052] ii. Synthesis of core-shell Fe / MOF@MOF precursor
[0053] 200 mg Fe / MOF was dispersed in 50 mL methanol, recorded as solution C. 0 g Cu(C5H7O2)2 was added to 50 mL methanol and ultrasonicated for 10 minutes, recorded as solution D. 0.657 g C4H6N2 was added to 20 mL methanol and dissolved, recorded as solution E. Subsequently, solutions D and E were slowly poured into C, stirred slowly for 12 hours, recorded as solution F. Then 0.58 g Zn(NO3)2·6H2O was added to 20 mL methanol and ultrasonically dispersed for 10 minutes, recorded as solution G. Then solution G was added to solution F and stirred slowly for 6 hours. After the reaction was completed, the precipitate was collected by centrifugation at 9000 rpm, washed 3 times with methanol, and the obtained product was dried overnight under vacuum to obtain a light yellow solid, which was the core-shell Fe / MOF@MOF precursor.
[0054] 2. Synthesis of core-shell FeNC@NC catalysts
[0055] The core-shell Fe / MOF@MOF precursor was placed in a tube furnace under Ar atmosphere and pyrolyzed at 900°C for 2 hours to obtain the core-shell FeNC@NC catalyst.
[0056] Comparative Example 2: Synthesis of core-shell NC@CuNC catalyst
[0057] 1. Synthesis of core-shell MOF@Cu / MOF
[0058] i. Synthesis of core layer MOF precursors
[0059] 1.16g of Zn(NO3)2·6H2O and 0g of Fe(C5H7O2)3 were dissolved in 50mL of methanol and ultrasonicated for 10min, which was recorded as solution A. 1.314g of C4H6N2 was dissolved in 50mL of methanol, which was recorded as solution B. Then solution A was slowly poured into solution B and stirred slowly for 12h. After the reaction was completed, the precipitate was collected by centrifugation at 9000rpm and washed three times with methanol. The obtained product was dried overnight under vacuum to obtain a light yellow solid, which was the core layer MOF.
[0060] ii. Synthesis of core-shell MOF@Cu / MOF precursor
[0061] 200 mg of core layer MOF was dispersed in 50 mL of methanol, which was recorded as solution C. 0.1 g of Cu(C5H7O2)2 was added to 50 mL of methanol, and the mixture was ultrasonicated for 10 minutes to make it evenly dispersed, which was recorded as solution D. 0.657 g of C4H6N2 was added to 20 mL of methanol to dissolve, which was recorded as solution E. Subsequently, solutions D and E were slowly poured into C respectively, and slowly stirred for 12 hours, which was recorded as solution F. Then 0.58 g of Zn(NO3)2·6H2O was added to 20 mL of methanol, ultrasonically dispersed for 10 minutes, which was recorded as solution G. Then solution G was added to solution F and slowly stirred for 6 hours. After the reaction was completed, the precipitate was collected by centrifugation at 9000 rpm, washed 3 times with methanol, and the obtained product was dried overnight under vacuum to obtain a light yellow solid, which was the core-shell MOF@Cu / MOF precursor.
[0062] 2. Synthesis of core-shell NC@CuNC catalysts
[0063] The core-shell MOF@Cu / MOF precursor was placed in a tube furnace under Ar atmosphere and pyrolyzed at 900 °C for 2 h to obtain the core-shell NC@CuNC catalyst.
[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for preparing an oxygen reduction catalyst for constructing a local "quasi-alkaline" microenvironment, characterized in that: The following steps are involved: (1) Fe is loaded on the core MOF material to obtain the core Fe / MOF material, and then the metal atom M with water activation ability is in situ constructed on the shell MOF material by epitaxial growth method to obtain the core-shell structured Fe / MOF@M / MOF precursor material, in which Fe and M are confined in the core and shell, respectively; (2) The Fe / MOF@M / MOF precursor material was subjected to in situ carbon conversion by pyrolysis to obtain the FeNC@MNC oxygen reduction catalyst that constructed a local "quasi-alkaline" microenvironment in natural seawater.
2. The method for preparing an oxygen reduction catalyst for constructing a local "quasi-alkaline" microenvironment according to claim 1, characterized in that: In step (1), the metal atom M having the ability to activate water is at least one of Cu, Ni, and Zn.
3. The method for preparing an oxygen reduction catalyst for constructing a local "quasi-alkaline" microenvironment according to claim 1, characterized in that: In step (2), the pyrolysis temperature is 800-1000° C., and the pyrolysis time is 1-4 hours.
4. The method for preparing an oxygen reduction catalyst for constructing a local "quasi-alkaline" microenvironment according to claim 1, characterized in that: In step (1), the MOF materials in the core Fe / MOF material and the shell M / MOF material are both ZIF-8.
5. The method for preparing an oxygen reduction catalyst for constructing a local "quasi-alkaline" microenvironment according to claim 4, characterized in that: The preparation process of the core Fe / MOF material is as follows: Dissolve Zn(NO3)2·6H2O and Fe(C5H7O2)3 in methanol and disperse them by ultrasonic, which is called solution A. Dissolve C4H6N2 in methanol and call it solution B. Pour solution A into solution B slowly and stir slowly. After the reaction is completed, collect the precipitate by centrifugation, wash it with methanol several times, and vacuum dry it overnight to obtain the core Fe / MOF material.
6. The method for preparing an oxygen reduction catalyst for constructing a local "quasi-alkaline" microenvironment according to claim 4, characterized in that: The preparation process of the Fe / MOF@M / MOF precursor material with a core-shell structure is as follows: The core Fe / MOF material is dispersed in methanol, which is recorded as solution C; Cu(C5H7O2)2 is dissolved in methanol and dispersed by ultrasonic, which is recorded as solution D; C4H6N2 is dissolved in methanol, which is recorded as solution E; Solution D and Solution E are slowly poured into Solution C respectively, and slowly stirred, which is recorded as solution F; Zn(NO3)2·6H2O is dissolved in methanol and dispersed by ultrasonic, which is recorded as solution G; Solution G was added to solution F and stirred slowly. After the reaction was completed, the precipitate was collected by centrifugation, washed several times with methanol, and vacuum dried overnight to obtain the Fe / MOF@M / MOF precursor material with a core-shell structure.
7. The method for preparing an oxygen reduction catalyst for constructing a local "quasi-alkaline" microenvironment according to claim 1, characterized in that: In step (1), the mass ratio of Fe, core MOF material, M and shell MOF material is 5:30:1:
10.
8. An oxygen reduction catalyst for constructing a local "quasi-alkaline" microenvironment, characterized in that: An oxygen reduction catalyst for constructing a local "alkaline-like" microenvironment prepared by the method described in any one of claims 1 to 7.
9. Use of the oxygen reduction catalyst for constructing a local "quasi-alkaline" microenvironment as claimed in claim 8 in seawater metal-air batteries.
Citation Information
Patent Citations
Core-shell CO oxidation catalyst as well as preparation method and application thereof
CN109759063A
ZIF-8-derived hollow Fe / Cu-N-C type oxygen reduction catalyst and preparation method and application thereof
CN110752380A
M-N / C composite material coated with phenolic resin shell layer and preparation method and application thereof
CN116742021A
Preparation method of double-monatomic electro-catalysis material and application of double-monatomic electro-catalysis material in zinc-air battery
CN118231691A